Coaxial cell printing of a human glomerular model: an in vitro glomerular filtration barrier and its pathophysiology. (1st April 2023) - Singh, Narendra K; Kim, Jae Yun; Lee, Jae Yeon; Lee, Hyungseok; Gao, Ge; Jang, Jinah; Kim, Yong Kyun; Cho, Dong-Woo
Abstract: Much effort has been expended in emulating the kidney's glomerular unit because of its limitless potential in the field of drug screening and nephrotoxicity testing in clinics. Herein, we fabricate a functional bilayer glomerular microvessel-on-a-chip that recapitulates the specific arrangement of the glomerular endothelial cell, podocyte layers, and the intervening glomerular basement membrane (GBM) in a single step. Our perfusable chip allows for the co-culture of monolayer glomerular endothelium and podocyte epithelium, which display mature functional markers of glomerular cells, and their proper interactions produce GBM proteins, which are the major components of the GBM in vivo . Furthermore, we test the selective permeability capacity, a representative hallmark function of the glomerular filtration barrier. Lastly, we evaluate the response of our glomerular model to Adriamycin- and hyperglycemia-induced injury to evaluate its applicability for drug screening and glomerular disease modeling.